INVESTIGATING THE PROLIFERATION AND SOCIO-POLITICAL RAMIFICATIONS OF MISINFORMATION IN CROSS RIVER STATE: A COMPREHENSIVE ANALYSIS OF ITS IMPACT ON CIVIC ENGAGEMENT AND ELECTORAL PARTICIPATION (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2025)
This study investigates the proliferation of misinformation in Cross River State, Nigeria, and its socio-political ramifications on civic engagement and electoral participation. Utilizing a mixed-methods approach, primary data were collected through surveys and focus group discussions with 500 participants across urban and rural demographics. Findings reveal that misinformation, primarily disseminated through social media platforms like WhatsApp and Facebook, significantly undermines trust in electoral institutions, fuels ethnic and religious tensions, and suppresses voter turnout. Approximately 68% of respondents reported encountering false information during the 2023 elections, with 45% indicating it influenced their voting decisions. Young voters (18–35 years) and those with lower educational attainment were most susceptible. The study highlights how misinformation exacerbates political apathy, discourages civic participation, and threatens democratic integrity. Recommendations include enhancing digital literacy programs, strengthening regulatory frameworks for social media, and fostering inclusive civic education to bolster electoral trust and participation. This research contributes to understanding misinformation’s role in shaping democratic processes in Nigeria’s diverse socio-political landscape.